The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/bmt.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of donor chimerism following myeloablative and nonmyeloablative allogeneic hematopoietic SCT

Abstract: Surveillance of hematopoietic chimerism following hematopoietic SCT (HSCT) with nonmyeloablative (NMA) preparative regimens is standard to assess the need for clinical intervention. Monitoring of donor chimerism following HSCT with myeloablative (MA) preparative regimens is, however, not considered useful because engraftment is thought to occur rapidly and consistently. This study compares the timing of donor hematopoietic cell engraftment in patients undergoing NMA conditioning with fludarabine and TBI with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…When no full donor chimaerism was achieved by day þ 28 or graft failure was suspected, the analysis was repeated at regular intervals. 25 DNA was extracted from both peripheral blood granulocytes and sorted CD3 þ T-lymphocytes, and STR sequences were analysed with a commercially available kit (AmpFlSTR Profiler Plus KIT, Applied Biosystems, Warrington, UK). Complete donor chimaerism was defined as more than 99% donor cells.…”
Section: Patientsmentioning
confidence: 99%
“…When no full donor chimaerism was achieved by day þ 28 or graft failure was suspected, the analysis was repeated at regular intervals. 25 DNA was extracted from both peripheral blood granulocytes and sorted CD3 þ T-lymphocytes, and STR sequences were analysed with a commercially available kit (AmpFlSTR Profiler Plus KIT, Applied Biosystems, Warrington, UK). Complete donor chimaerism was defined as more than 99% donor cells.…”
Section: Patientsmentioning
confidence: 99%
“…In reduced-intensity conditioning SCT, which is known to have a greater rate of graft loss than myeloablative SCT, chimerism is a measure of engraftment and can predict graft loss (Ozyurek et al, 2008). A recent study showed, however, that those receiving RIC conditioning generally attained full donor chimerism at a similar rate as those receiving myeloablative conditioning (Mickelson et al, 2011). The authors rightly assert that the role of chimerism surveillance is unclear at this time and, given the great variability of institutional practices, the issue needs to be addressed.…”
Section: Discussionmentioning
confidence: 94%
“…FAM, fluorescein amidite; BHQ, black hole quencher. receiving a nonmyeloablative conditioning regimen, donor lymphocyte infusions, or second transplantation [24,25]. In the present study, we developed a rapid SNP-based chimerism analysis method involving SNP genotyping by droplet-AS-PCR pre-HSCT samples and quantitation of recipient DNA using AS-qPCR for SNP genotype following HSCT.…”
Section: Discussionmentioning
confidence: 99%